10) \( 2(4 x-3)^{\frac{5}{4}}+9=495 \)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To solve the equation \( 2(4x - 3)^{\frac{5}{4}} + 9 = 495 \), we start by isolating the term with the exponent: 1. Subtract 9 from both sides: \[ 2(4x - 3)^{\frac{5}{4}} = 486 \] 2. Divide both sides by 2: \[ (4x - 3)^{\frac{5}{4}} = 243 \] 3. Raise both sides to the power of \(\frac{4}{5}\): \[ 4x - 3 = 243^{\frac{4}{5}} \] 4. To calculate \(243^{\frac{4}{5}}\), we can note that \(243 = 3^5\): \[ 243^{\frac{4}{5}} = (3^5)^{\frac{4}{5}} = 3^4 = 81 \] 5. Now we have: \[ 4x - 3 = 81 \] 6. Add 3 to both sides: \[ 4x = 84 \] 7. Divide by 4: \[ x = 21 \] Thus, the solution to the equation is \( x = 21 \).